Analysis of Effectiveness of Lean Management in Improvement of Service in Installation Nutrition RSUD dr. Iskak Tulungagung - Ida Srijani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Quality of nutrition installation service is determined from four processes; food planning, food preparation, food preparation, food processing and food distribution to patients. Efforts to improve service quality are modified processes using LEAN management. Pre experimental research design with one group pretest - post test design. Sample 36 people from all nutrition installation officer of food management system (MSPM) with sampling technique Non probability sampling type purposive sampling. The result of the research shows the influence of LEAN management implementation to the aspect of meal planning before and after intervention with wilcoxon test (p = 0,083) with pre test value 100% (good quality) and pos test value 100% good quality. In receipt aspect, preparation and storage of food obtained wilcoxon test (p = 0,157) with pre test value 100% enough quality and post test value 100% good quality. In the aspect of foodstuff processing obtained wilcoxon test (p = 0,001) with pre test value 100% enough quality and post test value 100% good quality. In the aspect of food distribution, the test of wilcoxon (p = 0,000) with pre test of 100% quality is sufficient and the post test value is 21%, the remaining quality is 79% good quality.